2017
DOI: 10.1042/bst20160183
|View full text |Cite
|
Sign up to set email alerts
|

The sweet tooth of the circadian clock

Abstract: The endogenous circadian clock is a key regulator of daily metabolic processes. On the other hand, circadian clocks in a broad range of tissues can be tuned by extrinsic and intrinsic metabolic cues. The bidirectional interaction between circadian clocks and metabolism involves both transcriptional and post-translational mechanisms. Nuclear receptors exemplify the transcriptional programs that couple molecular clocks to metabolism. The post-translational modifications of the core clock machinery are known to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…O-GlcNAcylation of cellular protein is sensitive to nutrient input [25, 49]. Since we observed that PER O-GlcNAcylation is higher during the day and gradually decreases over the circadian cycle, we expect that this temporal pattern may correlate to daily feeding activity.…”
Section: Resultsmentioning
confidence: 96%
“…O-GlcNAcylation of cellular protein is sensitive to nutrient input [25, 49]. Since we observed that PER O-GlcNAcylation is higher during the day and gradually decreases over the circadian cycle, we expect that this temporal pattern may correlate to daily feeding activity.…”
Section: Resultsmentioning
confidence: 96%
“…31 Another metabolism-related PTM includes protein O-GlcNAcylation, which has been reported to be circadian regulated in various tissues, including the heart. 55,176 Evidence suggests that BMAL1, CLOCK, PER1/2, and CRY1/2 are all O-GlcNAc modified, affecting their stability, cellular locality, and activity. 176 In the case of BMAL1, 24-hour rhythms in protein O-GlcNAcylation peak in the heart during the active period.…”
Section: Metabolism As An Integral Circadian Clock Feedback Loopmentioning
confidence: 99%
“…55,176 Evidence suggests that BMAL1, CLOCK, PER1/2, and CRY1/2 are all O-GlcNAc modified, affecting their stability, cellular locality, and activity. 176 In the case of BMAL1, 24-hour rhythms in protein O-GlcNAcylation peak in the heart during the active period. 55 Moreover, pharmacological perturbation of cardiac O-GlcNAcylation results in a rapid phase shift of the heart clock, consistent with a functional consequence of the PTM on the clock mechanism.…”
Section: Metabolism As An Integral Circadian Clock Feedback Loopmentioning
confidence: 99%
“…CRY and PER accumulate and form a dimer (CRY:PER) that inhibits CLOCK:BMAL1 activity. Adapted from [92]…”
Section: Introductionmentioning
confidence: 99%